Parameters predicting for prostate specific antigen response rates at one year post low-dose-rate intraoperative prostate brachytherapy - Martell, Kevin; Meyer, Tyler; Sia, Michael; Angyalfi, Steve; Husain, Siraj (Journal of Contemporary Brachytherapy, 2017)
Purpose: To develop a model for prostate specific antigen (PSA) values at one year among patients treated with intraoperatively planned 125 I prostate brachytherapy (IOPB). Material and methods : Four hundred and deven patients treated with IOPB for prostate adenocarcinoma were divided into four groups: those with PSA values ≥ 3 ng/ml; < 3 and ≥ 2; < 2 and ≥ 1 or PSA < 1 between 10.5 and 14.5 months post implantation (1yPSA). Ordinal regression analysis was then performed between patient, tumor, and treatment characteristics. 1yPSA values were also compared with toxicity outcomes. Results : Median 1yPSA was 0.77 (0.04-17.36). Thirty-two patients (8%) had a PSA ≥ 3; 35 (9%) had PSA < 3, ≥ 2; 87 (21%) had PSA < 2, ≥ 1, and most patients 254 (62%) had PSA < 1. PSA response was independent of gland volume, Gleason score, clinical stage, seed activity, V 90 , V 200 , D 90 , or number of needles and seeds used. Older patients had significantly lower 1yPSA; median ages 65.1 (46.5-81.0), 62.1 (50.4-79.5), 60.5 (47.1-80.3), and 58.1 (45.1-74.2) years for each of the 1yPSA groups respectively (p < 0.001). Also, both implant V 150 (p < 0.001) and initial PSA values (p = 0.04) were predictive of 1yPSA values. There was no correlation between 1yPSA values and toxicity encountered. Conclusions : PSA response at 1 year post IOPB appears to be dependent on patient age, initial PSA, and implant V 150 . Our results provide reassurance that parameters other than biochemical failure influence 1yPSA values.